2012
DOI: 10.1186/1471-2407-12-497
|View full text |Cite
|
Sign up to set email alerts
|

Hypofractionated stereotactic radiotherapy of limited brain metastases: a single-centre individualized treatment approach

Abstract: BackgroundWe retrospectively report treatment results of our single-centre experience with hypofractionated stereotactic radiotherapy (hfSRT) of limited brain metastases in primary and recurrence disease situations. Our aim was to find the most effective and safe dose concept.MethodsFrom 04/2006 to 12/2010, 75 patients, with 108 intracranial metastases, were treated with hfSRT. 52 newly diagnosed metastases (48%), without up-front whole brain radiotherapy (WBRT), received hfSRT as a primary treatment. 56 meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
(45 reference statements)
1
20
0
Order By: Relevance
“…Of the studies that looked at different dosing regimens, Aoyama et.al reported an association between the isocenter dose \35 Gy or peripheral dose \32 Gy with lower local control in univariate analysis, though this factor was no longer significant in their multivariate analysis [41]. OS overall survival, LC local control, LR local recurrence, HR hazard ratio, WBRT whole brain radiotherapy, SRT stereotactic radiotherapy, Gyn gynecologic, GI gastrointestinal, Gy gray, fx fractions EQD 2 [35 Gy had superior local control to those who did not (57 vs. 22 % at 1 year), though there was no significant difference in local control between the different dose concepts they examined [37]. However, in two additional studies in which several SRT doses were used, radiation dose was not associated with local control or survival [31,33].…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…Of the studies that looked at different dosing regimens, Aoyama et.al reported an association between the isocenter dose \35 Gy or peripheral dose \32 Gy with lower local control in univariate analysis, though this factor was no longer significant in their multivariate analysis [41]. OS overall survival, LC local control, LR local recurrence, HR hazard ratio, WBRT whole brain radiotherapy, SRT stereotactic radiotherapy, Gyn gynecologic, GI gastrointestinal, Gy gray, fx fractions EQD 2 [35 Gy had superior local control to those who did not (57 vs. 22 % at 1 year), though there was no significant difference in local control between the different dose concepts they examined [37]. However, in two additional studies in which several SRT doses were used, radiation dose was not associated with local control or survival [31,33].…”
Section: Discussionmentioning
confidence: 74%
“…At our institution, we use 25 Gy in 5 fractions most commonly, which is the most commonly used SRT fractionation regimen used in the United States according to a national survey of radiation oncologists who treat brain metastases with SRS/SRT [28]. The average reported local control rate after SRT is approximately 78 % (range 52-100 %) [15,[29][30][31][32][33][34][35][36][37][38][39][40], though many of the studies did not specifically isolate patients who did and did not receive WBRT. Two studies directly compared SRS with SRT, and there was no significant difference in local control or survival [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is difficult to compare the results of these studies due to the large hetereogeneity of the fractionation regimens. A recent report comparing different dose concepts in SHRT showed that EQD2s of ≥35 Gy seem to be the most effective concept in patients with primary or recurrent limited primary brain metastases [14]. We compared SRS to different hypofractionated regimens and failed to find any fractionation-associated differences in LC due to the high diversity of dose concepts.…”
Section: Frameless Image-guided Srs and Shrtmentioning
confidence: 89%
“…Metastatic brain tumors comprise of nearly 20-40% of all patients diagnosed with cancer [3][4]. As per current evidence, the primary treatment approaches for metastatic brain tumors include surgery, whole brain radiation therapy (WBRT), and stereotactic radiosurgery (SRS) [3][4][5]. WBRT has remained the primary treatment for patients presenting with high intracranial tumor burden.…”
Section: Discussionmentioning
confidence: 99%